2023
DOI: 10.12681/jhvms.27821
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigation of the nutritional composition of two commercial fish species: Rainbow trout (Oncorhynchus mykiss) and Atlantic salmon (Salmo salar)

Abstract: In this study, it was aimed to compare of nutritional composition, cholesterol, trans fatty acids, fatty acids, lipid quality index, vitamins (A, B9, B2, B12, D3), selenium (Se), and iron (Fe) contents between farmed Atlantic salmon and rainbow trout. Crude protein, crude fat, carbohydrate, and energy values of Atlantic salmon were slightly higher than rainbow trout while crude ash and moisture values were higher in rainbow trout (p < 0.05). The cholesterol content of samples in rainbow trout and Atlantic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Fish meat is a food with a very low carbohydrate content. Various researchers were reported the carbohydrate content of Atlantic salmon as 0.19g/100g (Şengör et al, 2013) and 1.72% (Kocatepe et al, 2022). In the production of Atlantic salmon meatballs, the additives added to the meatball batter increased the carbohydrate content of the final product up to 7.87 g/100g.…”
Section: Proximate Composition Of Fish Meatballsmentioning
confidence: 99%
“…Fish meat is a food with a very low carbohydrate content. Various researchers were reported the carbohydrate content of Atlantic salmon as 0.19g/100g (Şengör et al, 2013) and 1.72% (Kocatepe et al, 2022). In the production of Atlantic salmon meatballs, the additives added to the meatball batter increased the carbohydrate content of the final product up to 7.87 g/100g.…”
Section: Proximate Composition Of Fish Meatballsmentioning
confidence: 99%
“…B2 content was twice that of this literature. Kocatepe et al (2022) reported that the vitamin A content of large rainbow trout was higher than Atlantic salmon. The folate content of the groups was similar to the salmon folate content and was given as 10 µg/100g by (Dias et al, 2003).…”
Section: Vitamins Minerals and Heavy Metals Content Of The Groupsmentioning
confidence: 99%